Using system dynamics for collaborative design: a case study - von Koch Lena; Putilova Mariya; Elf Marie; Öhrn Kerstin (BMC, 2007)
Abstract Background In order to facilitate the collaborative design, system dynamics (SD) with a group modelling approach was used in the early stages of planning a new stroke unit. During six workshops a SD model was created in a multiprofessional group. Aim To explore to which extent and how the use of system dynamics contributed to the collaborative design process. Method A case study was conducted using several data sources. Results SD supported a collaborative design, by facilitating an explicit description of stroke care process, a dialogue and a joint understanding. The construction of the model obliged the group to conceptualise the stroke care and experimentation with the model gave the opportunity to reflect on care. Conclusion SD facilitated the collaborative design process and should be integrated in the early stages of the design process as a quality improvement tool.